MAQASID Al-SHARI’AH SEBAGAI PENDEKATAN PENAFSIRAN AL-QUR’AN : MAQASID Al-SHARI’AH SEBAGAI PENDEKATAN PENAFSIRAN AL-QUR’AN - Zamroji, Muhamad (LPPM IAI Hasanuddin Pare-Kediri, 2023)
In developing of Qur'anic interpretation, the main problem of meaning is concerned with the two basic principle, namely the universality (generality) of the text al-'ibra>h bi umum al-alfaz bi khusus al-sabab which is based on the bayani reasoning of the text and the particular meaning (specificity) of the text (al-'ibrah bi umum al-sabab la bi khusus al-alfaz which is based on contextual reasoning of the text known as the contemporary interpretation approach . As an alternative, there needs to be a new rule in the interpretation of the Qur'an, namely (al-'ibrah bi maqasid al-shari'ah), which in its interpretation adheres to the purpose of establishing an understanding of verses by law. Therefore, the verses of the Koran must be understood in terms of moral messages or maqasid al-shari'ah. This is what became known as al-tafsir maqasid al-shari'ah (interpreting the Koran using the maqasid al-shari'ah approach). So the maqasid al-shari'ah doctrine is an effort to uphold maslahah as an essential element in legal objectives so that it colors the more progressive activities of interpreting al-Qur'anic texts. It is this academic reason that makes the writer try to discuss the steps of maqashid sharia which are connected with the basis of maslahah interconnectivity. From the explanation above it appears that al-maqasid which is an axiology of Islamic law has been brought to the realm of epistemology so that it becomes an independent scientific discipline. This maqasid al-shari'ah is able to engage in dialectic with the problems of contemporary law that are always developing.